Congenital scrub typhus: a case report and literature review - Pinghua Liang; Zengling Su; Min Chen; Min Chen; Sitao Li; Sitao Li; Sitao Li (Frontiers Media S.A., 2023)
BackgroundThis study aimed to analyze the clinical course of a newborn with congenital scrub typhus caused by vertical transmission and explore early diagnosis and treatment strategies. The clinical data of the neonate were retrospectively analyzed and the related literature was reviewed.Case presentationThe newborn was a full-term one, with a good Apgar score at birth. The neonate had apnea at 3 h of life, requiring NICU care and IV antibiotics (piperacillin) for suspected sepsis. An examination revealed hepatosplenomegaly. Blood tests revealed anemia and thrombocytopenia and a chest x-ray showed patchy inflammation. On the second day of life, he developed a fever. On the third day of life, he required mechanical ventilation because his condition worsened after he presented with dyspnea, hypotension, depressed sensorium, and other signs of sepsis. Importantly, the neonate's mother had a history of scrub typhus at 31+ weeks of gestation. While the blood culture result was still pending, high-throughput sequencing of blood and cerebrospinal fluid was performed. To address the suspected scrub typhus infection, oral azithromycin dry suspension was added to the treatment regimen. High-throughput sequencing results on the 5th day of life confirmed a significant presence of 16SrRNA sequences in the blood, suggesting an Orientia tsutsugamushi infection. The neonate steadily recovered and was discharged 16 days after hospitalization. The neonate was followed up for 9 months, and the outcome was favorable with normal growth and development.ConclusionsThis article reports a case of congenital Orientia tsutsugamushi infection, a rare condition caused by vertical transmission. Our review of the literature, combined with the presented case, brings the total number of documented congenital scrub typhus cases caused by vertical transmission to eight. Regrettably, one patient from this group unexpectedly died on the 10th day of hospitalization, resulting in a mortality rate of 12.5% (1/8). The special transmission mode and clinical manifestations of this disease will serve as an alert to doctors for timely diagnosis and treatment. Because of the non-specific clinical manifestations of congenital scrub typhus, limited understanding, low index of suspicion among clinicians, and a lack of diagnostic facilities, scrub typhus is seriously underdiagnosed in pregnant women, fetuses, and neonates.